Efektivitas Pemungutan Retribusi Tempat Rekreasi dan Olahraga Kabupaten Bogor - Indra Sumarna Sobari (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2020)
Receipt of retribution from recreation and sports venues in Bogor Regency annually corrects the decline. Therefore, this study aims to analyze the effectiveness of retribution collection on recreational and sports sites. This research is a qualitative study with data collection techniques in the form of interviews, observation and written document. The results of the study indicate that this levy was less effective in 2018. This was caused by poor quality human resources and inadequate infrastructure facilities.